Transfer of mycotoxins in the food chain - Mézes, Miklós (Animal welfare, Ethology and Housing Systems (AWETH), 2015)
Mould infection of the feed plants may produce mycotoxins in adequate environmental condition. Those mycotoxins cause health risk for farm animals and those have food safety risk concern for human consumers with animal origin foods. Occurrence of mycotoxins in animal origin foods is different because the different rate of metabolism and accumulation of mycotoxins in farm animals and their edible tissues.Among the important mycotoxins in feed plants and consequently in animal origin foods the highest danger is the presence of aflatoxin B1 and its hydroxylated metaolite, excreted with milk or egg, aflatoxin M1, because the high carry-over rate. Mycotoxins of Fusarium moulds, such as deoxynivalenol, T-2 and HT-2 toxin, and zearalenone, has lower human food safety risk through animal origin foods, because of their low carry-over and accumulation rate. In contrary, another fusariotoxin, fumonisin, may arise higher food safety risk, because its absorption rate is low, but accumulate effectively in edible tissues for a long period of time, therefore fumonisins can be found in animal origin foods. Similarly, feeding farm animals with ochratoxin A contaminated diet a higher rate of accumulation can be found in some edible tissues of farm animals.
Keywords: mycotoxin; food chain; animal origin foods